Assessing the reliability of local buckling of plates for mild and high strength steels. (March 2018) - Schillo, N.; Taras, A.; Feldmann, M.
Abstract: In the current Eurocode 3-1-5 [1 ] for local buckling, the resistance curve used to represent the reduction factor of plated elements due to local failure is based on the so-called Winter-curve, derived on a semi-empirical approach by George Winter in 1947. This design curve represents the mean reduction values achieved in the experiments conducted by Winter and other researchers. However, when applying the safety concept of EN 1990 [2 ], an additional safety factor γ M is necessary to ascertain a defined level of failure probability. Currently, this factor is set to 1.0 for applications in building structures. In this paper 34 stub column tests on welded, squared box sections of steel grade S500 up to S960 are described. In combination with an experimental database on stub column tests summarised in Ref. [3], a new, optimised resistance curve is derived which could act as an alternative to the Winter curve. Additionally, both functions are evaluated in regard to the safety standard EN 1990 [2] with focus on the resulting γ M . As γ M represents the safety factor for the actual material and geometric properties, which are not known by the designer, the more decisive safety factor is γ M * . This factor is used throughout Eurocode and refers to the nominal material and geometric properties. Its derivation and the influencing parameters are discussed and evaluated in the study at hand. Highlights: The background and history for the design of local buckling of plates are presented. A reliability analysis is performed assessing the formulas in the current EC3-1-5. An improved resistance curve with respect to the safety requirements of EN 1990 and the existing experimental results is developed. The standard resistance curve and the new developed resistance curve are compared in terms of reliability. For both approaches, the safety factor γ M * is derived.